16th Review of Master's Theses in the Field of the History of Pharmacy - Anna Trojanowska; Elżbieta Rutkowska (Polish Pharmaceutical Society, 2022)
The Historical Section of the Polish Pharmaceutical Society and Institute for the History of Science of the Polish Academy of Sciences have been organizing Reviews of master's theses in the field of the history of pharmacy since 2006. Two master's theses were presented during the 16th Review. Sandra Fabianowska presented the topic of Antiepileptic medicines in the light of Polish medical journals from the second half of the 19th and the first half of the 20th century (Poznań 2021). Katarzyna Maria Galon reported the work titled The problems of contemporary pharmacy in the pages of the "Aptekarz" journal in the years 1993-2006 (Warsaw 2021). The Historical Section of the Polish Pharmaceutical Society and Institute for the History of Science of the Polish Academy of Sciences have been organizing Reviews of master's theses in the field of the history of pharmacy since 2006. Two master's theses were presented during the 16th Review. Sandra Fabianowska presented the topic of Antiepileptic medicines in the light of Polish medical journals from the second half of the 19th and the first half of the 20th century (Poznań 2021). Katarzyna Maria Galon reported the work titled The problems of contemporary pharmacy in the pages of the "Aptekarz" journal in the years 1993-2006 (Warsaw 2021). The Historical Section of the Polish Pharmaceutical Society and Institute for the History of Science of the Polish Academy of Sciences have been organizing Reviews of master's theses in the field of the history of pharmacy since 2006. Two master's theses were presented during the 16th Review. Sandra Fabianowska presented the topic of Antiepileptic medicines in the light of Polish medical journals from the second half of the 19th and the first half of the 20th century (Poznań 2021). Katarzyna Maria Galon reported the work titled The problems of contemporary pharmacy in the pages of the "Aptekarz" journal in the years 1993-2006 (Warsaw 2021). The Historical Section of the Polish Pharmaceutical Society and Institute for the History of Science of the Polish Academy of Sciences have been organizing Reviews of master's theses in the field of the history of pharmacy since 2006. Two master's theses were presented during the 16th Review. Sandra Fabianowska presented the topic of Antiepileptic medicines in the light of Polish medical journals from the second half of the 19th and the first half of the 20th century (Poznań 2021). Katarzyna Maria Galon reported the work titled The problems of contemporary pharmacy in the pages of the "Aptekarz" journal in the years 1993-2006 (Warsaw 2021). The Historical Section of the Polish Pharmaceutical Society and Institute for the History of Science of the Polish Academy of Sciences have been organizing Reviews of master's theses in the field of the history of pharmacy since 2006. Two master's theses were presented during the 16th Review. Sandra Fabianowska presented the topic of Antiepileptic medicines in the light of Polish medical journals from the second half of the 19th and the first half of the 20th century (Poznań 2021). Katarzyna Maria Galon reported the work titled The problems of contemporary pharmacy in the pages of the "Aptekarz" journal in the years 1993-2006 (Warsaw 2021).